2009
DOI: 10.1021/jm801374t
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Antitubercular Nitroimidazoles. 2. Determinants of Aerobic Activity and Quantitative Structure−Activity Relationships

Abstract: The (S)-2-nitro-6-substituted 6,7-dihydro-5H-imidazo[2,1-b][1,3]oxazines have been extensively explored for their potential use as new antituberculars based on their excellent bactericidal properties on aerobic whole cells of Mycobacterium tuberculosis. An oxygen atom at the 2-position of the imidazole ring is required for aerobic activity. Here we show that substitution of this oxygen by either nitrogen or sulfur yielded equipotent analogs. Acylating the amino series, oxidizing the thioether, or replacing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
107
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(112 citation statements)
references
References 30 publications
5
107
0
Order By: Relevance
“…A C C E P T E D ACCEPTED MANUSCRIPT 4 polar isosteres of isonicotinic acid, which may be due to better penetration of these agents into the cell wall of the mycobacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 4 polar isosteres of isonicotinic acid, which may be due to better penetration of these agents into the cell wall of the mycobacteria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Among these two moieties, 2-nitroimidazo- [2, 1-b] [1,3]oxazines show excellent pharmacokinetics, tolerability, and safety in clinical trials [7]. The SAR studies reported on this group are also reasonably limited [8][9][10][11]. The studies indicate that bicyclic oxazines, the lipophilic tail and the oxygen substituents are the key components required for activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…The studies indicate that bicyclic oxazines, the lipophilic tail and the oxygen substituents are the key components required for activity [10]. Replacement of oxygen by sulfur also produces active compounds but replacement with sulfoxide or sulfone or with carbon dramatically reduces the activity [11,12]. Planche et al [13] reported two models for the design and prediction of new antituberculosis agents to overcome resistance of Mycobacterium tuberculosis to the existing drugs.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Due to his pharmacological activities, the synthesis of new nitroimidazole compounds remains as a very active area of research. [4][5][6] It is a well known matter that the biological activity of nitroimidazole compounds is related to the redox chemistry of the nitro group. 7 This aspect has motivated a great number of electrochemical studies and consequently, the redox chemistry of different nitro compounds of biological significance is focused to understand how the reduction of the nitro group can play an active role in several aspects as: electroanalytical determinations, free radical generation, stability and reactivity.…”
Section: Introductionmentioning
confidence: 99%